(untitled) (Ameghiniana, 2013)
"In the last years considerable new record s of Jurassic and Cretaceous tetrapods from Argentina, Perú and Brazil give opportunity to have better knowledge of the faunal succession of the Mesozoic and to elaborate a few paleobiogeographical assumptions. Triassic. The 97% of the tetrapod taxa from this Period are recorded between the 28°S and the 35°S. This prevents any general paleobiogeographical assumption for the whole continent. The seven local faunas and the provincial ages based on them are commented. The faunistic percentage from the Lower Triassic Puestoviejense is of 9%, increasing through the Lower Chañarense (18%) and the upper Chañarense (29%), then decreasing through the Ischigualastense (26%) up to the Coloradense (17%). This fluctuation reflects the richness of taxa of the Middle Triassic made up of the final radiation of the Therapsida plus the first important radiation of the Archosauria. The proportion of the carnivorous and herbivorous species in each provincial age is discussed. The type of tetrapod assemblage and its enviroment for each provincial age is discussed. Jurassic. Five local faunas are recorded in the Jurassic plus several isolated findings. The record suggests that the whole continent was populated during this Period. The marine deposits from the 20°S up to the 40°S with Pterosaurs, Chelonians, Crocodiles and Ichthyosaurs suggest a marine coast with tropical waters. Cretaceous. Thirteen local faunas and many isolated taxa are recorded for the Cretaceous. They are distributed through the Period with one local fauna in the Neocomian, three in the Aptian-Albian and nine in the Senonian. The 75% of the Crocodiles species and the 70% of the amphibian Chelonians are recorded north of the 35°S. South to the same latitud the 63% of the Dinosaur taxa are recorded. lt suggests two different biogeographic zones during the Upper Cretaceous. The Ornithischian evidence suggests faunal connexions with North America in the Upper Cretaceous and probably with Africa in the Lower Cretaceous.